Pacific House (H.S. Crocker Co., Inc.)
Pacific House, theme building of the Pageant of the Pacific, overlooking the Great Lagoon at San Francisco's 1939 Golden Gate International Exposition on Treasure Island. Around the lagoon are grouped dramatic exhibit buildings of the Orient, the South Seas, and Latin America.